Seed germination of Quercus robur, q. pyrenaica and q. ilex and the effects of smoke, heat, ash and charcoal - Reyes, Otilia; Casal, Mercedes (Ann. For. Sci., 2006)
This study is centred on Quercus robur, Q. pyrenaica and Q. ilex that have a distribution area covering all Europe. Fire is a frequent ecological factor in many ecosystems, especially in those with Mediterranean climates. Our working hypothesis is that fire affects the germination process. An experiment was carried out testing the following treatments: Control, Smoke-5 min, Smoke-10min, Smoke-15 min, 60 ºC-5 min, 60 °C-15 min, 90 ºC-5 min, 110 ºC-5 min, 150 ºC-5 min, Ash, Ash Dilution and Charcoal. The seed incubation was spread over a year. The germination rates of the Control are very high, especially in Q. ilex. Almost none of the treatments inhibit germination and only the Q. ilex seeds, when subjected to 150 ºC-5 min, show a marked inhibition. Q. robur and Q. pyrenaica take a year to complete their germination, while Q. ilex only takes 22 weeks. Probably, this reproductive behaviour is related to the climate characteristics to which the species have become adapted. Finally, fire does not determine the germination process, the recruitment of new individuals being independent of fire.
Keywords: fire; germination; Quercus; reproductive strategies; Seeds

Seed germination of Quercus robur, q. pyrenaica and q. ilex and the effects of smoke, heat, ash and charcoal - Reyes, Otilia; Casal, Mercedes (Ann. For. Sci., 2006)
This study is centred on Quercus robur, Q. pyrenaica and Q. ilex that have a distribution area covering all Europe. Fire is a frequent ecological factor in many ecosystems, especially in those with Mediterranean climates. Our working hypothesis is that fire affects the germination process. An experiment was carried out testing the following treatments: Control, Smoke-5 min, Smoke-10min, Smoke-15 min, 60 ºC-5 min, 60 °C-15 min, 90 ºC-5 min, 110 ºC-5 min, 150 ºC-5 min, Ash, Ash Dilution and Charcoal. The seed incubation was spread over a year. The germination rates of the Control are very high, especially in Q. ilex. Almost none of the treatments inhibit germination and only the Q. ilex seeds, when subjected to 150 ºC-5 min, show a marked inhibition. Q. robur and Q. pyrenaica take a year to complete their germination, while Q. ilex only takes 22 weeks. Probably, this reproductive behaviour is related to the climate characteristics to which the species have become adapted. Finally, fire does not determine the germination process, the recruitment of new individuals being independent of fire.
Keywords: fire; germination; Quercus; reproductive strategies; Seeds

Breeding performance of the Blue Tit Parus caeruleus in a patchy Mediterranean landscape - Catalan, R M; Haeger, J F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1999)
This study compares reproductive strategy and breeding success of Parus caeruleus in a helm-oak (Quercus rotundifolia) forest and a pine plantation (Pinus pinea and P. pinaster) in the southern Iberian Peninsula. During the breeding period, an asymmetric flow of individuals takes place from the helm-oak forest to the pine plantation. This flow is favoured by nestboxes where Blue tits can lay their eggs. During the winter, a large part of the population moves back from the pine plantation to the helm-oak forest. Breeding pair density was much higher in the helm-oak forest than in the pine plantation. This may bt accounted for by the poorer quality of the resources available in the pine plantation which birds try to compensate for with larger breeding territories. Breeding density and most life-history traits examined (timing of breeding, clutch site, egg size, number of fledglings and fledgling weight) were similar in both habitats, as a result of the phenotypic plasticity of this species. Although breeding success was similar in both habitats, recruitment of new individuals per unit area was higher in the helm-oak forest. The consequences of pine plantations, as a form of forestry management, on species conservation is discussed.
APS
Keywords: breeding success; Holm oak; iberian peninsula; Parus caeruleus; Pinus pinaster; Pinus pinea; Quercus ilex; reproductive strategies

Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J A; de Rio, J M; Valdecantos Garcia, J L; Santamaria, I G (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies

Ecological aspects of the floral phenology of the cork-oak (Q suber L): why do annual and biennial biotypes appear? - Elena-Rossello, J. A.; de Rio, J. M.; Valdecantos Garcia, J. L.; Santamaria, I. G. (Ann. For. Sci., 1993)
Phenological observations (periods of flowering and pollination, floral structures, etc) were made over a 3-year period in natural populations of Q suber. We demonstrated the existence of 2 different types of seed cycles in the cork-oak. The 'annual biotype', requires only 1 season to complete its reproductive cycle (ie, similar to that of the Lepidobalanus group), whereas the 'biennial biotype' requires 2 full years (similar to Erythrobalanus). The variability observed in the cork-oak, during the reproductive cycle, and the meaning of the existence of 2 different reproductive strategies in the same species, are discussed
Keywords: annual and biennial biotypes; cork-oak; ecological variability; floral phenology; Quercus; reproductive strategies